A bidirection-adjustable ionic current rectification system based on a biconical micro-channel. Issue 83 (4th September 2015) - Chang, Fengxia; Chen, Cheng; Xie, Xia; Chen, Lisha; Li, Meixian; Zhu, Zhiwei
Abstract : We developed a simple, cheap and bidirectional ionic current rectification system based on the integration of a biconical micro-channel, working electrode and reference electrode. This system may have potential and realistic future value for studying two-way ionic transport in the cell membrane. Abstract : We developed a simple, cheap and bidirectional ionic current rectification system based on the integration of a biconical micro-channel, working electrode and reference electrode. This system may have potential and realistic future value for studying two-way ionic transport in the cell membrane.